An arrayed genome‐wide perturbation screen identifies the ribonucleoprotein Hnrnpk as rate‐limiting for prion propagation. (18th October 2022) - Avar, Merve; Heinzer, Daniel; Thackray, Alana M; Liu, Yingjun; Hruska‐Plochan, Marian; Sellitto, Stefano; Schaper, Elke; Pease, Daniel P; Yin, Jiang‐An; Lakkaraju, Asvin KK; Emmenegger, Marc; Losa, Marco; et al.
Abstract: A defining characteristic of mammalian prions is their capacity for self‐sustained propagation. Theoretical considerations and experimental evidence suggest that prion propagation is modulated by cell‐autonomous and non‐autonomous modifiers. Using a novel quantitative phospholipase protection assay (QUIPPER) for high‐throughput prion measurements, we performed an arrayed genome‐wide RNA interference (RNAi) screen aimed at detecting cellular host‐factors that can modify prion propagation. We exposed prion‐infected cells in high‐density microplates to 35, 364 ternary pools of 52, 746 siRNAs targeting 17, 582 genes representing the majority of the mouse protein‐coding transcriptome. We identified 1, 191 modulators of prion propagation. While 1, 151 modified the expression of both the pathological prion protein, PrP Sc, and its cellular counterpart, PrP C, 40 genes selectively affected PrP Sc . Of the latter 40 genes, 20 augmented prion production when suppressed. A prominent limiter of prion propagation was the heterogeneous nuclear ribonucleoprotein Hnrnpk. Psammaplysene A (PSA), which binds Hnrnpk, reduced prion levels in cultured cells and protected them from cytotoxicity. PSA also reduced prion levels in infected cerebellar organotypic slices and alleviated locomotor deficits in prion‐infected Drosophila melanogaster expressing ovine PrP C . Hence, genome‐wide QUIPPER‐based perturbations can discover actionable cellular pathways involved in prion propagation. Further, the unexpected identification of a prion‐controlling ribonucleoprotein suggests a role for RNA in the generation of infectious prions. Synopsis: A systematic analysis for cellular host‐factors involved in prion propagation has been missing due to the lack of a compatible high‐throughput detection method. This study describes the development and application of a novel prion detection assay and identifies new host‐factors involved in prion propagation. The QUantItative Prion PhospholipasE pRotection assay (QUIPPER) allows for prion detection in cultured cells in a high‐throughput format. A genome‐wide screen in prion infected mouse cells identifies new host factors for prion propagation. Hnrnpk/HNRNPK limits prion formation in mouse and human cells. The compound Psammaplysene A can reduce prion formation in vitro and in vivo . Abstract : A novel quantitative phospholipase protection assay in combination with a genome‐wide RNA interference screen leads to the identification of host factors involved in prion propagation.